TITLE CHALLENGES OF GENDER DISCRIMINATION AND PAY INEQUALITY ENCOUNTERED BY WOMEN IN SOUTH AFRICAN WORKPLACES - Phoke Alpha Rakgwata; Turmelo Sekgobela (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Women experience various challenges that leads to gender inequality. The patriarchal system in various countries subject women to slavery and undue pressure. Globally, women continue to be subject of inequality and are not treated the same way that other genders would. Religion, culture, norms and customs are some of the elements that contribute to the challenges faced by women throughout the world. The patriarchal system believes in subjecting women to have less rights as compared to the male gender. The purpose of this paper was to address the challenges faced by women in their workplaces on daily basis. It further sought to challenge the perception about women incompetence in performance of their duties. Gender equality will achieve its intended purpose when there is diversity and equal treatment of all genders. The study adopted the qualitative research approach to gain better understanding of the phenomenon within the natural setting. The ecological theory was used as a theoretical framework to understand the gender discrimination, inequality and pay gap. The theory was applied to bring foundation and confirm the findings of the study. The study found that South African workplace is vulnerable for gender discrimination, inequality and pay gap. Transformation of the workplace should be prioritized to be inclusive of all genders. It further highlighted the importance of the implementations of the existing policies.